THE EFFECT OF USING THE ACCOUNTING INFORMATION SYSTEM IN IMPROVING THE ORGANIZATION’S PERFORMANCE - S. Mohamad, Idris; J. Bakr, Dzoar (International Journal of Psychosocial Rehabilitation, 2020)
This paper evaluates the importance of accounting information systems (AIS) and information technology in accounting practices. Previous findings revealed that many firms are losing vast amounts of money on processing accounting information. Additionally, the management of these companies does not have access to real-time financial information for decision-making and financial forecasting. There is a need, therefore, to assess the importance of AIS in the accounting department of a firm. This study employed qualitative and quantitative research methods to collect and analyze research data. In total, 19 participants drawn from 7 companies within the Zakho district met the eligibility criteria, which required that participants be owners or employees of the selected companies. The results showed that many companies within the Zakho district have deployed AIS and are carrying out accounting practices faster. There is proper planning and coordination of financial information and thus efficiency in decision-making.